The mediating role of compassion in the relationship between COVID-19 anxiety syndrome and COVID-19 burnout - Esmaeil Mousavi Asl; Hatam Boostani; Forouzan Behrouzian; Hamzeh Rostami (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The coronavirus has caused fundamental changes in our way of life, leading to a wave of psychological distress associated with the COVID-19 epidemic, including stress, anxiety, perceived threats, and fear. Considering the psychological consequences of COVID-19, the present study was conducted with the aim of mediating the role of compassion in the relationship between COVID-19 anxiety syndrome and COVID-19 burnout. MATERIALS AND METHODS: The design of the present study was descriptive correlation. The present study population included all students of Ahvaz Jundishapur University of Medical Sciences in the academic year 2020. Two hundred and fifty-one students were selected and completed the COVID-19 Anxiety Syndrome Questionnaire, Compassion Scale, and COVID-19 Burnout Scale. Pearson correlation coefficient test and structural equation model were performed using SPSS version 18 and LISREL 8.8. RESULTS: The results showed that COVID-19 burnout had a positive and significant relationship with the overall score of anxiety syndrome (r = 0.42, P = 0.01), while it has a negative and significant relationship with compassion (r = −0.37, P = 0.01). Compassion also has a significant negative relationship with anxiety syndrome (r = −0.35, P = 0.01). In addition, the results of path analysis showed that compassion plays a mediating role in the relationship between COVID-19 anxiety syndrome and COVID-19 burnout. CONCLUSION: Based on the findings of the present study, it can be said that compassion acts as a protective factor against the negative effects of anxiety syndrome. Therefore, this factor can be considered in the development of prevention and treatment programs for burnout caused by COVID-19.